Martes americana Turton 1806 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Martes americana Turton 1806 Martes americana Turton 1806, in: Linnaeus, Gen. Syst. Nat., Vol. 1: 60. Type Locality: "North America". Vernacular Names: American Marten. Subspecies:: Subspecies Martes americana subsp. americana Turton 1806 Subspecies Martes americana subsp. abieticola Preble 1902 Subspecies Martes americana subsp. abietinoides Gray 1865 Subspecies Martes americana subsp. actuosa Osgood 1900 Subspecies Martes americana subsp. atrata Bangs 1897 Subspecies Martes americana subsp. caurina Merriam 1890 Subspecies Martes americana subsp. humboldtensis Grinnell and Dixon 1926 Subspecies Martes americana subsp. kenaiensis Elliot 1903 Subspecies Martes americana subsp. nesophila Osgood 1901 Subspecies Martes americana subsp. origensis Rhoads 1902 Subspecies Martes americana subsp. sierrae Grinnell and Storer 1916 Subspecies Martes americana subsp. vancourverensis Grinnell and Dixon 1926 Subspecies Martes americana subsp. vulpina Rafinesque 1819 Distribution: Canada, USA (Alaska to N California, south in the Sierra Nevada and Rocky Mtns to 35°N, Maine, Minnesota, New York). Conservation: IUCN – Lower Risk (lc). Discussion: May be conspecific with martes , melampus , and zibellina (Anderson, 1970; Hagmeier, 1961). Reviewed by Clark et al. (1987) who considered New World forms as a distinct species agreeing with Youngman (1975). Carr and Hicks (1997) recognized two distinct species based on genetic data ( M. americana – Eastern North America; M. caurina – Pacific Northwest and the Great Plains). However, most have recognized that there are two distinct subspecies groups – " caurina " and " americana " (Anderson, 1970; Clark et al., 1987; Graham and Graham, 1994; Hagmeier, 1961; Stone and Cook, 2002). Synonyms allocated according to Hall (1981) and Clark et al. (1987). Stone and Cook (2002) placed in the subgenus Martes . Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, ...